Pengaruh Perputaran Aktiva Terhadap Pertumbuhan Laba Industri Rokok yang Terdaftar di Bursa Efek Indonesia - . Nurhadi (SOSIALITA, 2011)
Growth in earnings is one of the information that describes the prospects of the business. Assets turnover ratio is an indicator used to measure the effectiveness of the use of corporate assets. This study aims to determine the effect turnover of fixed assets and current assets on earnings growth. The population in this study is the cigarette companys financial statements listed in Indonesia Stock Exchange in 2009. The sampling technique using a purposive sampling. Data collection techniques in this research uses documentary techniques. The independent variables include: Inventory Turn Over, Working Capital Turn Over, Fixed Assets and Total Assets Turn Over. Dependent variable is earnings growth. The data analysis technique in this study using multiple linear regression analysis. The results prove that the simultaneous analysis of independent variables significant effect on earnings growth. Partially known that the Fixed Assets Turn Over, Total Assets Turn Over and Working Capital Turn Over significantly affect earnings growth. While Turn Over Inventory does not significantly affect earnings growth.